2013
DOI: 10.2528/pier12100406
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Characterization of the Yeast Cell Budding Cycle

Abstract: Abstract-We combine experimental electrorotation data and the numerical analysis of the electrorotation chamber and cell to electrically characterize the Saccharomyces cerevisiae yeast budding cell cycle and to obtain the electrical parameters of the cell. To model the yeast cell we use spherical and doublet-shaped geometries with a four layered structure: cytoplasm, membrane, inner and outer walls. To derive the geometrical and electrical parameters of the yeast model we use the finite element method to calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…U wb is the average potential applied to the experiment, U box is the potential applied to the simulation box in order to simulate the current density j . n.a.=not applicable, E. coli values from [48] , [49] , S. cerevisiae values from [50] , B. subtilis subtilis thickness values from [51] and values for permittivity and conductivity are approximated by values for S. aureus and S. epidermidis from [52] , [48] , respectively. Cytoplasm values for THP-1 monocytes are derived from [53] , membrane values from [54] .…”
Section: Resultsmentioning
confidence: 99%
“…U wb is the average potential applied to the experiment, U box is the potential applied to the simulation box in order to simulate the current density j . n.a.=not applicable, E. coli values from [48] , [49] , S. cerevisiae values from [50] , B. subtilis subtilis thickness values from [51] and values for permittivity and conductivity are approximated by values for S. aureus and S. epidermidis from [52] , [48] , respectively. Cytoplasm values for THP-1 monocytes are derived from [53] , membrane values from [54] .…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies showed that the DEP characteristic of yeast cells varies widely, depending on the cell size, shape, and electric properties of cell contents and membrane. 18,31 In particular, the reported values of the crossover frequency where the value of Re(b) of the cell changes its sign (e.g., from negative to positive) have a range that spans one order of magnitude of the field frequency. This situation may be prominent for cultured yeast cells because of the budding process, which leads to a change in shape and size during growth.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, plant cells, Gram-negative bacteria like Escherichia coli ( E. coli ), and fungi like Saccharomyces cerevisiae ( S. cerevisiae ) have outer cell walls. The electrical model of these cells could be represented by “multi-shell model” [ 31 ]. Based on MMT, these electrical models could be simplified step by step until it becomes a homogeneous sphere according to following equation: where R i ( i = 1, 2, 3, 4) and ( i = 1, 2, 3, 4) are the radius and the complex permittivity of each shell.…”
Section: Theory and Modelingmentioning
confidence: 99%